Study of Awareness and Perception Regarding MOOC Courses with Special Reference to NPTEL - Amit kumar Arora; Santosh Kumar (New Delhi Assoicated Management Consultants Pvt Ltd, 2024)
The study aimed to determine the level of awareness among students regarding NPTEL MOOC's and the reason for registering or not registering for the courses. Further this study explored the impact of gender and qualification of aware respondents. The data were collected from Delhi NCR Region from janaury to march 2023.The Study found that receiving the certificate being more convenient regarding timing and location and having command over the subject were the perceived benefits of NPTEL courses. The main reason for not finishing the course were time constraints. students poor course selection. and loss of momentum as the course progressed. Gender was found to be independent of the category of aware respondents while qualification was not found to be independent. It was recommended that colleges, universities adopt blended learning which included e learning as well as face to face learning to help students score more. The study recommended that students be careful while choosing the course and complete the course to earn certificate which can enhance their curriculum and in turn help them get a good job
Keywords: Online Learning; MOOC; Distance Education; NPTEL